Attitudes in Fiji towards varieties of English. Issue 4 (12th August 2015) - Hundt, Marianne; Zipp, Lena; Huber, André
ABSTRACT: In Schneider's (2007) influential model, the emergence of positive attitudes towards the local, post‐colonial variety is an important step for the evolution of new Englishes, not least of all because it is likely to mark a shift from an external towards an internal norm. This paper explores attitudes towards varieties of English among a group of young Fiji citizens in tertiary education. The results indicate that British English is still a strong reference variety, while American English is clearly favoured over more local Pacific varieties, like Australian and New Zealand English. A closer analysis of the survey data indicates that a simple dichotomy of exo‐ vs. endonormative orientation may be difficult to maintain in this context.